Clubes barriales de la ciudad de Santa Fe: diagnóstico y prognosis - Azerrad, María Rut (Ediciones UNL. Secretaría de Extensión de la UNL, 2020)
The purpose of this article is to present a diagnosis of the situation of one hundred sports clubs located in different neighbourhoods of Santa Fe city, which arises from a fieldwork carried out jointly by the elective and optional course Social and Solidarity Economy and a Social Interest Extension Project from the School of Economic Sciences (FCE) of Universidad Nacional del Litoral (UNL). This research aimed to meet a demand from the Secretariat of Social Development of the local Government, the Undersecretariat of Sports and, more specifically, the Directorate of Sports and the Clubs Programme. Subsequently, based on the diagnosis, we present the methodological proposal to work with these organisations by accompanying them and by developing strategies for a continuous and comprehensive literacy process.